Advances in nanoplasmonic biosensors for clinical applications. Issue 24 (30th October 2019) - Mauriz, Elba; Dey, Priyanka; Lechuga, Laura M.
Abstract : Plasmonic biosensors can be conveniently used as portable diagnostic devices for attaining timely and cost-effective clinical outcomes. Nanoplasmonics technology opens the way for sensor miniaturization, multiplexing and point of care testing. Abstract : Biomarkers are unquestionable biological indicators for diagnosis and therapeutic interventions providing appropriate classification of a wide range of health disorders and risk factors. Nonetheless, the detection and quantification of biomarkers need to be tested with sufficient reliability by robust analytical methods in order to assure clinical performance in health care settings. Since the analytical performance is determined by the sensitivity and specificity of the method employed, techniques have been intensively refined in order to avoid the misinterpretation of results and undesirable bias. Although biomarkers can be detected with the existing analytical techniques, to reproducibly quantify them in decentralized settings or remote locations with the required accuracy is still a challenge. Currently, only a few point-of-care devices for biomarker evaluation are commercially available. Thus, more focused research efforts are needed to overcome these limitations in order to provide universal patient-centered care platforms. To this end, plasmonic biosensors can be conveniently used as portable diagnostic devices for attaining timely and cost-effective clinical outcomes. The development of enhanced performance based on nanoplasmonics technology opens the way for sensor miniaturization, multiplexing and point of care testing. This review covers recent advances and applications of plasmonic and nanoplasmonic biosensors intended for biomarker diagnosis in clinical practice, including cancer, cardiovascular and neurodegenerative diseases. The review specially focuses on: (i) recent progress in plasmonics development including the design of singular nanostructured surfaces, (ii) novel chemical functionalization strategies for the appropriate incorporation of bioreceptors and (iii) plasmonic applications as real operative devices in the clinical field. Future prospects in the use of nanoplasmonic sensor platforms for personalised quantification and management of biomarkers directly in body fluids will also be discussed.